Grape seed extract attenuates hyperglycaemia-induced in rats by streptozotocin - Sally A. El-Awdan; Gehad A. Abdel Jaleel; Dalia O. Saleh (Faculty of Pharmacy, Cairo University, 2013)
The current study aimed to investigate the possible beneficial effects of grape seed extract (GSE) on some metabolic and biochemical changes associated with streptozotocin (STZ; 50 mg/kg; i.p.)-induced hyperglycaemia in male rats. Blood samples were used to determine serum levels of glucose, insulin, total cholesterol (TC) and triglycerides (TG). Some biochemical markers for oxidative stress viz., serum lipid peroxides level (measured as malondialdehyde; MDA) and total antioxidant capacity as well as serum nitric oxide (NO) level were assessed. Hyperglycaemic animals received GSE (100 and 300 mg/kg/day) orally on daily basis for 28 consecutive days and their effects were determined 24 h after the administration of the last dose. Results of the present study revealed that STZ-induced hyperglycaemia is associated with decreased serum insulin level with increased levels of TC and TG. Hyperglycaemia was also associated with increased level of serum MDA together with decreased total antioxidant capacity and level of serum NO. GSE succeeded to improve the serum glucose level in STZ-treated rats in a dose dependent manner. It also showed a restoration of the increased serum level of TC, TG and MDA and of the suppressed insulin and total antioxidant capacity as well as the decreased plasma level of NO. From our results it can be concluded that GSE has beneficial effects against the biochemical changes associated with STZ-induced hyperglycaemia. These beneficial effects might be related to the ability of GSE to improve hyperglycaemia in addition to its anti-oxidant property.